Effect of tofacitinib on pain, fatigue, health-related quality of life and work productivity in patients with active ankylosing spondylitis: results from a phase III, randomised, double-blind, placebo-controlled trial. Issue 2 (2nd June 2022) - Navarro-Compán, Victoria; Wei, James Cheng-Chung; Van den Bosch, Filip; Magrey, Marina; Wang, Lisy; Fleishaker, Dona; Cappelleri, Joseph C; Wang, Cunshan; Wu, Joseph; Dina, Oluwaseyi; Fallon, Lara; Strand, Vibeke
Abstract : Background: Ankylosing spondylitis (AS) impacts quality of life. We assessed patient-reported outcomes (PROs), pain, fatigue, health-related quality of life (HRQoL) and work productivity in a phase III trial of tofacitinib. Methods: Adults with AS and with inadequate response/intolerance to ≥2 non-steroidal anti-inflammatory drugs received tofacitinib 5 mg twice daily or placebo for 16 weeks. Afterwards, all received open-label tofacitinib until week 48. Change from baseline to week 48 was determined for PROs: total back pain; nocturnal spinal pain; Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) overall spinal pain (Q2); Functional Assessment of Chronic Illness Therapy-Fatigue; BASDAI fatigue (Q1); AS Quality of Life (ASQoL); Short Form-36 Health Survey Version 2 (SF-36v2); EuroQoL-Five Dimension-Three Level health profile and Visual Analogue Scale; and the Work Productivity and Activity Impairment (WPAI) questionnaire. Improvements from baseline ≥minimum clinically important difference, and scores ≥normative values at week 16 were evaluated. Results: In 269 randomised and treated patients, at week 16, there were greater least squares mean improvements from baseline with tofacitinib 5 mg twice daily versus placebo in BASDAI overall spinal pain (–2.85 vs –1.34), BASDAI fatigue (–2.36 vs –1.08), ASQoL (–4.03 vs –2.01) and WPAI overall work impairment (–21.49 vs –7.64) (all p<0.001); improvements continued/increased to week 48. Improved spinal pain with tofacitinib was seen by week 2. Patients receiving tofacitinib reported clinically meaningful PRO improvements at week 16. Percentages with PRO scores ≥normative values at week 16 were greater with tofacitinib in SF-36v2 Physical Component Summary, physical functioning and bodily pain domains (p≤0.05). Conclusions: In patients with AS, treatment with tofacitinib 5 mg twice daily resulted in clinically meaningful improvements in pain, fatigue, HRQoL and work productivity versus placebo to week 16, which were sustained to week 48. Trial registration number: NCT03502616 .